Microwave Attenuation in High Temperature Superconductors (International Journal of Scientific Research in Science and Technology, 2025)
Novel ab-initio theory of microwave attenuation in high temperature superconductors has been investigated by using the quantum dynamical approach of double-times temperature dependent electron Green’s functions technique. We have calculated the expressions for electron density of state (EDOS) via an almost complete Hamiltonian which includes the contributions of the unperturbed phonons and electrons, anharmonic phonon fields, localize phonon fields and that of electron phonon interaction. From these EDOS expressions, we have calculated the microwave attenuation for high temperature superconductors. We have observed that the main factors influencing microwave attenuation include temperature, electron-phonon coupling, phonon concentration, etc. The outcome is in good agreement with the experimental results.